Characterizing Head Acceleration Events in Law Enforcement Cadets During Subject Control Technique Training - Smith, Carly R.; Onate, James A.; Edwards, Nathan A.; Hagen, Joshua A.; Kolba, Chris; Paur, Scott; Walters, Joshua; Caccese, Jaclyn B. (Annals of biomedical engineering, 2024)
Law enforcement cadets (LECs) complete weeks of subject control technique training. Similar sport-related combat training has been shown to expose participants to head acceleration events (HAEs) that have potential to result in short- and long-term impairments. The purpose of this study was to describe the number and magnitude of HAEs in LECs throughout their training. 37 LECs (7 females; age = 30.6 ± 8.8 years; BMI = 30.0 ± 6.0) were recruited from a law enforcement organization. Participants wore instrumented mouthguards, which recorded all HAEs exceeding a resultant 5 g threshold for training sessions with the potential for HAEs. Participants completed three defensive tactics (DT) training sessions, a DT skill assessment (DTA), and three boxing sessions. Outcome measures included the number of HAEs, peak linear acceleration (PLA), and peak rotational velocity (PRV). There were 2758 true-positive HAEs recorded across the duration of the study. Boxing sessions accounted for 63.7% of all true-positive HAEs, while DT accounted for 31.4% and DTA accounted for 4.9%. Boxing sessions resulted in a higher number of HAEs per session ( F 2,28 = 48.588, p < 0.001, η p 2 = 0.776), and higher median PLA ( F 2,28 = 8.609, p = 0.001, η p 2 = 0.381) and median PRV ( F 2,28 = 11.297, p < 0.001, η p 2 = 0.447) than DT and DTA. The LECs experience a high number of HAEs, particularly during boxing sessions. Although this training is necessary for job duties, HAE monitoring may lead to modifications in training structure to improve participant safety and enhance recovery.